2012
DOI: 10.3389/fnsys.2012.00069
|View full text |Cite
|
Sign up to set email alerts
|

ADHD-200 Global Competition: diagnosing ADHD using personal characteristic data can outperform resting state fMRI measurements

Abstract: Neuroimaging-based diagnostics could potentially assist clinicians to make more accurate diagnoses resulting in faster, more effective treatment. We participated in the 2011 ADHD-200 Global Competition which involved analyzing a large dataset of 973 participants including Attention deficit hyperactivity disorder (ADHD) patients and healthy controls. Each participant's data included a resting state functional magnetic resonance imaging (fMRI) scan as well as personal characteristic and diagnostic data. The goal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
104
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(129 citation statements)
references
References 43 publications
10
104
1
1
Order By: Relevance
“…This has been variably successful, as indicated by the diverse outcomes from fMRI-based classification competitions. In these competitions, the accuracies of neuroimaging-based diagnoses have ranged from poor (e.g., attention deficit hyperactivity disorder; Brown et al, 2012) to excellent (e.g., schizophrenia; Silva et al, 2014). More importantly, however, the attempt to replace or augment traditional clinical diagnostics by applying machine learning techniques to neuroimaging data is a strategy of limited long-term clinical utility.…”
Section: Introductionmentioning
confidence: 98%
“…This has been variably successful, as indicated by the diverse outcomes from fMRI-based classification competitions. In these competitions, the accuracies of neuroimaging-based diagnoses have ranged from poor (e.g., attention deficit hyperactivity disorder; Brown et al, 2012) to excellent (e.g., schizophrenia; Silva et al, 2014). More importantly, however, the attempt to replace or augment traditional clinical diagnostics by applying machine learning techniques to neuroimaging data is a strategy of limited long-term clinical utility.…”
Section: Introductionmentioning
confidence: 98%
“…The approach of Eloyan et al (2012) predicted the test data diagnoses most accurately—among teams who used the imaging data. Surprisingly, however, Brown et al (2012) attained somewhat better predictive accuracy without using the images at all. My colleagues and I (Reiss et al, 2015) have shown how CV-based testing can be modified to assess whether image data adds predictive value beyond that offered by non-imaging predictors.…”
Section: Is Statistical Significance the Appropriate Aim?mentioning
confidence: 85%
“…A multi-site data sharing effort termed ADHD-200 [58], has recently resulted in publications with very large samples. For example, ADHD brains (n=757) exhibited altered RSFC between default network and ventral attention networks [59].…”
Section: Resting State Functional Connectivity Studies With Clinical mentioning
confidence: 99%